Predictors of breastfeeding self‐efficacy among women attending an urban postnatal clinic, Uganda. Issue 3 (21st March 2019) - Nankumbi, Joyce; Mukama, Ashely Atwiine; Ngabirano, Tom Denis
Abstract: Aim: The aim of this study was to determine the factors associated with breastfeeding self‐efficacy among postnatal women in Kampala, Uganda. Methods: This was a descriptive cross‐sectional study that was conducted among women attending a postnatal clinic at a teaching hospital in Kampala. Three hundred and eighty‐four postnatal women were randomly selected to respond to an interviewer‐administered questionnaire. We used the Breastfeeding Self‐Efficacy scale (BFSES) to assesses breastfeeding self‐efficacy (BFSE). Descriptive statistics and percentages were used to summarize the findings. Bivariate and multivariate logistic regressions were used to determine predictors of BFSE. Results: Participants had a mean BFSE score of 48.65. The 14 item BFSES consistently measured breastfeeding confidence with a Cronbach's alpha of 0.89. About six in 10 women (60.2%) had high BFSE, the rest (39.8%) had low BFSE. Having a partner (adjusted odds ratio (aOR): 13, 95% CI 3.46–15) and receiving breastfeeding support from health workers (aOR: 4.45, 95% CI: 1.95–6.12) were significantly associated with BFSE. Conclusion: A notable number of mothers had a low BFSE. Health workers should support breastfeeding mothers to achieve the desired exclusive breastfeeding levels. Relevance to clinical practice: The findings of the study provide a direction for midwives in maternity care in educating and supporting women about breastfeeding for the improvement of exclusive breastfeeding rates thus realization of benefits of exclusive breastfeeding.